Pediatric Chest Pain—Low-Probability Referral: A Multi-Institutional Analysis From Standardized Clinical Assessment and Management Plans (SCAMPs®), the Pediatric Health Information Systems Database, and the National Ambulatory Medical Care Survey. (November 2017) - Harahsheh, Ashraf S.; O'Byrne, Michael L.; Pastor, Bill; Graham, Dionne A.; Fulton, David R.
We conducted a study to assess test characteristics of red-flag criteria for identifying cardiac disease causing chest pain and technical charges of low-probability referrals. Accuracy of red-flag criteria was ascertained through study of chest pain Standardized Clinical Assessment and Management Plans (SCAMPs®) data. Patients were divided into 2 groups: Group1 (concerning clinical elements) and Group2 (without). We compared incidence of cardiac disease causing chest pain between these 2 groups. Technical charges of Group 2 were analyzed using the Pediatric Health Information System database. Potential savings for the US population was estimated using National Ambulatory Medical Care Survey data. Fifty-two percent of subjects formed Group 1. Cardiac disease causing chest pain was identified in 8/1656 (0.48%). No heart disease was identified in patients in Group 2 ( P = .03). Applying red-flags in determining need for referral identified patients with cardiac disease causing chest pain with 100% sensitivity. Median technical charges for Group 2, over a 4-year period, were US2014$775 559. Eliminating cardiac testing of low-probability referrals would save US2014$3 775 182 in technical charges annually. Red-flag criteria were an effective screen for children with chest pain. Eliminating cardiac testing in children without red-flags for referral has significant technical charge savings.